1996
DOI: 10.1063/1.868815
|View full text |Cite
|
Sign up to set email alerts
|

The curvature of material lines in chaotic cavity flows

Abstract: Material line folding is studied in two-dimensional chaotic cavity flows. Line folding is measured by the local curvature kϭl؋lЈ/͉l͉ 3 , where l(q) is an infinitesimal vector in the tangential direction of the line, q is a coordinate along the line, and lЈ is the derivative of l with respect to q. It is shown both analytically and numerically that folding is always accompanied by compression. The vector lЈ plays a crucial role as a driving force for the stretching and folding processes. A material line is stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

1997
1997
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…Such anticorrelation was also noticed by Boozer and coworkers [21], who, in their theory of finite-time Lyapunov exponents for chaotic flows, found that the local Lyapunov exponent of the flow was strongly suppressed in the regions of high curvature. Finally, results very similar to those surveyed above were obtained by Muzzio and coworkers [20] for a number of 2D and 3D deterministic chaotic flows. Thus, the exact theory of the curvature statistics that we have been able to develop in the framework of the Kazantsev-Kraichnan model incorporates all of the essential features thus far observed numerically, as well as surmised in less direct theoretical ways.…”
Section: Summary and Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Such anticorrelation was also noticed by Boozer and coworkers [21], who, in their theory of finite-time Lyapunov exponents for chaotic flows, found that the local Lyapunov exponent of the flow was strongly suppressed in the regions of high curvature. Finally, results very similar to those surveyed above were obtained by Muzzio and coworkers [20] for a number of 2D and 3D deterministic chaotic flows. Thus, the exact theory of the curvature statistics that we have been able to develop in the framework of the Kazantsev-Kraichnan model incorporates all of the essential features thus far observed numerically, as well as surmised in less direct theoretical ways.…”
Section: Summary and Discussionsupporting
confidence: 74%
“…The curvature statistics also appear to be largely insensitive to the type of flows considered. Thus, numerical simulations involving 3D forced [17] and 2D decaying [14] Navier-Stokes turbulence, Kraichnan's [42] random flow model [18,15], 2D and 3D deterministic but chaotic flows [20], and, finally, our own 3D forced-MHD simulations and theoretical results based on the Kazantsev-Kraichan velocity field (both compressible and incompressible), consistently reveal the same set of properties of the curvature distribution. The unbounded exponential growth of the mean-square curvature was first observed in the numerical studies of Pope and coworkers [17], who also found that, unlike the moments of the curvature itself, the moments of its logarithm tended to time-independent asymptotic values.…”
Section: Summary and Discussionmentioning
confidence: 90%
See 3 more Smart Citations